Comparative study of adnexal mass among ultrasonographic findings, perioperative findings and histopathological findings - Purabi, Ayesha Siddika; Ara, Shamim; Tasrin, Liza; Sultana, Jesmin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Adnexal malignancy is a significant diagnostic challenge in gynaecology and is the third most common cancer of the female genital tract after cervical and endometrial cancer. Accurate preoperative characterization of adnexal masses is crucial for appropriate management, surgical planning and patient referral. Ultrasonography is widely used as a first-line imaging modality because of its accessibility and low cost. This study aimed to assess the diagnostic correlation among ultrasonographic, peroperative and histopathological findings in adnexal masses. Methods: This prospective cross-sectional observational study was conducted at the Gynaecological Oncology Unit of Dhaka Medical College Hospital, Bangladesh, from July 2021 to June 2022. Seventy female patients aged 14-75 years with sonographically detected adnexal masses who underwent surgery were included. Ultrasonographic morphological features were evaluated preoperatively, intraoperative findings were documented and histopathology was used as a reference standard. Data were analyzed using SPSS version 23.0. Results: The mean age of the participants was 41.6±19.5 years and 65.7% were premenopausal. Ultrasonography classified 64.3% of masses as benign and 35.7% as malignant, whereas histopathology confirmed 68.6% of masses as benign and 31.4% as malignant. Ultrasonography demonstrated a sensitivity of 90.9%, specificity of 89.6% and overall accuracy of 90.0% compared with histopathology. Per-operative assessment showed comparable diagnostic performance. Conclusions: Ultrasonography is a reliable, sensitive and specific modality for preoperative evaluation of adnexal masses. Its effective use can facilitate early diagnosis, improve clinical decision-making and potentially enhance survival outcomes through timely and appropriate treatment.